Collecting Data of Late Recordings of Dragonflies in Poland in the Period of 2013-2020, as an Example of the Citizen Science - Tańczuk, Agnieszka; Tończyk, Grzegorz (Studia Ecologiae et Bioethicae, 2023)
The group “Ważki (Odonata) w Polsce” is an excellent example of citizen science, understood as a cooperation between society and professionals in scientific activity. The goal of the present paper is to show the data concerning the very late appearances of dragonflies and damselflies in the years 2013 – 2020, to enrich the knowledge about the phenology of various species in comparison to published data, which is no longer valid, taking into consideration the climatic changes over the last decades. It would not have been possible to gather such a great amount of information, if not for the amateurs engaged into a project like that (ca. 100 people). The data was catalogued according to date, place, and species. The main methods used were: the visual observation and taking photos of adult dragonflies. After thoroughly studying the data collected in early, middle, and late autumn (October, November, December), and analysing it carefully, the records were divided into three groups. The information gathered enables us to show the differences in phenology of some of the species. The project organised as a citizen science action, contributed to the increase of the knowledge concerning the late aspect of Polish odonato fauna.